"WAYANG PALEMBANG": ITS ORIGINS, CHARACTERISTICS, AND PRESERVATION FROM EXTINCTION - Rochmiatun, Endang (Journal of Malay Islamic Studies, 2019)
Wayang Palembang is a traditional art of performing arts with artificial media of people made of leather. Wayang Palembang contains universal cultural values because it tells human life. This study describes the existence of Wayang Palembang through manuscript traces (ancient manuscripts). The research found that the Wayang Palembang was originally introduced by the ruling elites of the ruling Majapahit kingdom in Palembang. During the time of Palembang Sultanate this art modified by absorbing elements of Malay culture. Subsequently, he continued to be preserved during colonial and post independence. Wayang Palembang has unique characteristics that distinguish it from Javanese puppet, which is from the aspect of the introduction language by the Mastermind, the display of its own, or the performance devices, including the duration of the timing. This shows the harmonious acculturation and adaptation between Javanese culture and Palembang Malay culture. The heyday of the Palembang puppet period ended in 1980, with the last Dalang death